Administrasi Manajemen Kurikulum Intrakurikuler dan Ekstrakurikuler Dalam Menanamkan Karakter Siswa di SD Al-Ittihadiyah Laut Dendang - Aziz, Mursal; Namira, Adinda Nadda; Siregar, Dewi Chairunnisa; Khatulistiwa (Administraus, 2024)
Character education is an effort to apply religious, moral, and ethical values to students through knowledge with the help of parents, teachers, and the community. This is very important for the formation and development of student character. Because every child has extraordinary potential from birth, but this potential must continue to be honed and socialized so that their character is fully formed and developed. Due to changes occurring in social, technological, and cultural dynamics today, character education is becoming increasingly important. This is because new challenges arise in building individuals who have strong moral, ethical, and personality principles. This research aims to explore and analyze the effectiveness of cultivating student character through intracurricular and extracurricular activities at SD Al-Ittihadiyah Laut Dendang. The type of research method used is a descriptive method with a qualitative approach. Data was collected through observation, interviews, and analysis of library literature. The results of the research show that intracurricular and extracurricular activities at SD Al-Ittihadiyah Laut Dendang are effective in instilling student character. Activities, such as learning activities, religious activities, and sports activities make a significant contribution to the formation of student character, such as honesty, discipline, cooperation, and responsibility. The implication of this research is how important it is to develop intracurricular and extracurricular activity programs that focus on cultivating student character in elementary schools.